Stenotrophomonas maltophilia promotes lung adenocarcinoma progression by upregulating histone deacetylase 5 - Shen, Jiyu; Ni, Yalan; Guan, Qijie; Li, Rui; Cao, Hong; Geng, Yan; You, Qingjun (Frontiers in Microbiology, 2023)
Introduction Lung cancer is the leading cause of cancer death worldwide, and lung adenocarcinoma (LADC) is the most common lung cancer. Lung cancer has a distinct microbiome composition correlated with patients’ smoking status. However, the causal evidence of microbial impacts on LADC is largely unknown. Methods We investigated microbial communities’ differences in Formalin-Fixed Paraffin-Embedded tissues of ever-smoke (n = 22) and never-smoke (n = 31) patients with LADC through bacterial 16S rRNA gene high-throughput sequencing. Then nitrosamines 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)-induced lung cancer mouse model and A549 cells were used to study the effect of Stenotrophomonas maltophilia (S. maltophilia) in LADC. Results and Discussion We found a significant increase of genus Stenotrophomonas in LADC tissues of patients with primary tumor size greater than 3 cm and never-smoker patients. We further found that intratracheal infection with S. maltophilia promoted tumor progression in the NNK-induced lung cancer mouse model. We performed RNA-seq analysis on lung tissues and found that S. maltophilia treatment drove inflammation and upregulated tumor associated cell signaling, including Apelin signaling pathway. Mechanistically, histone deacetylase 5 (HDAC5) gene expression was significantly upregulated in S. maltophilia treated groups, and was required for S. maltophilia induced cell proliferation and migration in LADC cell line A549. Therefore, we provide in vivo and in vitro evidence to demonstrate that S. maltophilia promotes LADC progression, in part, through HDAC5.